The Evolution of the Faculty of History at University of Bucharest (1970-1989). Case Study: A look into the professionalization of history graduates through the analysis of study programmes - GHEBOIANU, Matei (Studia Universitatis Babeș-Bolyai Historia, 2020)
The Evolution of the Faculty of History at University of Bucharest (1970-1989). Case Study: A look into the professionalization of history graduates through the analysis of study programmes. In this article I will analyse the evolution of the Faculty of History within the University of Bucharest from 1970-1989, from the perspective of the admission process, the changes that have occurred among the study programs, the number of students and the provision of the skills necessary for graduates to become good professionals in the domain. Rezumat: Evoluţia Facultăţii de Istorie a Universităţii din Bucureşti (1970-1989). Studiu de caz: O privire asupra profesionalizării absolvenţilor de istorie prin analiza programelor de studiu. În acest articol voi analiza evoluţia Facultăţii de Istorie din cadrul Universităţii din Bucureşti între anii 1970-1989, din perspectiva procesului de admitere, modificările care au avut loc în programele de studiu, numărul de studenţi şi modalitatea în care au fost dezvoltate abilităţile necesare ale absolvenţilor pentru a deveni buni profesionişti ai domeniului. Cuvinte cheie: istorie, istorie-filozofie, studenţi, educaţie, Partidul Comunist Român